Developing a Creative Learning Model to Increase Middle School Students’ Interest in Reading - Amin Zaki; Nurul Huda; Syafiq Amir (Yayasan Adra Karima Hubbi, 2024)
The decline in reading interest among middle school students is a growing concern in the field of education. Despite the increasing availability of digital content, traditional reading remains critical for developing cognitive and analytical skills. Previous studies have highlighted the need for innovative learning models to engage students and foster a love for reading. This study aims to develop and evaluate a creative learning model designed to enhance middle school students’ interest in reading. The model focuses on incorporating interactive and engaging activities that connect reading materials with students’ daily lives and interests. A mixed-method approach was used, combining qualitative and quantitative data collection techniques. The sample consisted of 150 middle school students from three schools. A pretest-posttest design was employed to assess changes in students’ reading interest, complemented by interviews and observations for qualitative insights. The findings revealed a significant increase in students’ interest in reading, as evidenced by improved survey scores and positive feedback from both students and teachers. The creative learning model effectively engaged students, making reading more enjoyable and relevant to their personal experiences. The creative learning model proved successful in increasing middle school students’ reading interest. It emphasizes the importance of developing innovative teaching strategies to foster a lasting interest in reading, contributing to improved academic outcomes.